Indigenous People, Economic Development and Sustainable Tourism: A Comparative Analysis between Bali, Indonesia and Australia - Putri Triari; Kali Jones; Ni Gusti Ayu Dyah Satyawati (Faculty of law Udayana University, 2017)
Tourism is one of the world’s fastest growing industries and has been used as a vehicle for indigenous people to engage in economic development opportunities within their local communities. The concept of sustainable tourism has brought greater awareness towards maintaining the economic and social advantages of tourism development whilst ensuring the industry is both socio-cultural and environmentally sustainable. A central component to the definition of sustainable tourism is the empowerment of indigenous people to take advantage of the benefits of the tourism industry. This article will demonstrate that in certain instances there is conflict between indigenous peoples’ culture, particularly communal ownership of land and the tourism industry. This research uses comparative analysis between Bali, Indonesia and the Northern Territory of Australia to analyse the social and legal impediments, which affect the potential of local indigenous people to contribute to sustainable tourism. The conclusion drawn in this article is that both Indonesia and Australia have attempted to provide legal frameworks to promote tourism and development alongside indigenous people, however in both cases the tourism industry has not always been easily applicable to indigenous people’s concept of land ownership and communal sharing of economic assets. Keywords: Indigenous People, Tourism, Bali, Australia